Steady State Performance Investigation of a Three Phase Induction Motor Running Off Unbalanced Supply Voltages - Jalal Abdi, Aslan Sabahaldeen (Al-Khwarizmi Engineering Journal, 2011)
The objective of this work is to investigate the performance of a conventional three phase induction motor supplied by unbalanced voltages. An effort to study the motor steady state performance under this disturbance is introduced. Using per phase equivalent circuit analysis with the concept of symmetrical components approach, the steady state performance is theoretically calculated. Also, a model for the induction motor with the MATLAB/Simulink SPS tools has been implemented and steady state results were obtained. Both results are compared and show good correlation as well. The simulation model is introduced to support and enhance electrical engineers with a complete understanding for the steady state performance of a fully loaded induction motor operating from unbalanced supply voltages.